2021
DOI: 10.2147/itt.s260429
|View full text |Cite
|
Sign up to set email alerts
|

VISTA: A Promising Target for Cancer Immunotherapy?

Abstract: Agents targeting the B7 family co-inhibitory receptors cytotoxic T-lymphocyte antigen-4 (CTLA-4) and programmed cell death protein-1 (PD-1), or its ligand (PD-L1), have a pivotal role in clinical practice. V-domain Ig suppressor of T-cell activation (VISTA) is a protein highly conserved between species, with a similar amino acid sequence to the B7 family members, characterized by a particularly structural homology to PD-1. It has been counted as an emerging target within the list of novel targetable immune che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 83 publications
0
34
1
Order By: Relevance
“…The statistical analysis of the immunostaining in the FFPE FMC samples revealed a higher expression of VISTA in cancer cells when compared to TILs ( p < 0.0001), contrary to what is reported in a variety of human cancers [ 29 , 32 , 43 , 44 , 63 , 64 ]. Interestingly, a positive correlation was obtained by the increase in VISTA expression in cancer cells and TILs ( p = 0.0022), which suggests a paracrine mechanism used by cancer cells to communicate with the immune system, as reported for PD-L1 in breast cancer patients [ 65 , 66 , 67 ].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The statistical analysis of the immunostaining in the FFPE FMC samples revealed a higher expression of VISTA in cancer cells when compared to TILs ( p < 0.0001), contrary to what is reported in a variety of human cancers [ 29 , 32 , 43 , 44 , 63 , 64 ]. Interestingly, a positive correlation was obtained by the increase in VISTA expression in cancer cells and TILs ( p = 0.0022), which suggests a paracrine mechanism used by cancer cells to communicate with the immune system, as reported for PD-L1 in breast cancer patients [ 65 , 66 , 67 ].…”
Section: Discussioncontrasting
confidence: 76%
“…In these samples, a homogenous VISTA expression was observed in TILs, while in cancer cells a heterogeneous VISTA expression was obtained, according to the findings in human cancers. Thus, this result indicates different cancer cell subpopulations that vary in their genetic, phenotypic, or behavioral characteristics, being associated with cancer progression and therapeutic resistance [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Observations in malignant settings suggest that VISTA expression suppresses the T cell-mediated response and promotes immune evasion [79][80][81][82]. Additionally, it was reported that VISTA is mainly expressed on immune cells, especially CD8+ T cells, and is associated with immunosuppressive conditions in various tumor types, including melanoma, acute myeloid leukemia (AML), hepatocellular carcinoma (HCC), small-lung-cell carcinoma, gastric cancer, and colorectal cancer, as reviewed in detail by ElTanbouly et al [83] and Tagliamento et al [84].…”
Section: Co-inhibitory B7-cd28 Family Membersmentioning
confidence: 99%
“…Particularly, inhibitors of cytotoxic T lymphocyte antigen-4 (CTLA-4) and programmed death receptor (PD-1) and PD-ligand 1 (PD-L1) checkpoints, which regulate priming and effector phases of T-cell activation, respectively, were approved by the FDA ( Table 3 ) [ 182 ]. Clinical trials using other immune checkpoint inhibitors are ongoing, targeting T cell immunoglobulin and mucin-containing protein 3 (TIM-3) (NCT03311412, NCT02817633, NCT03307785) [ 183 , 184 ], lymphocyte activation gene-3 (LAG-3) (NCT03311412, NCT03538028, NCT03156114) [ 184 , 185 , 186 ], V-domain lg suppressor of T cell activation (VISTA) (NCT02671955, CTRI/2017/12/01 1026) [ 187 , 188 ], human endogenous retrovirus-h long terminal repeat-associating protein 2 (HHLA2), and T cell lg and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT) (NCT04746924, NCT04866017) [ 189 ]. Most of the ICIs proved a limited benefit with 10%–20% overall response rates of monotherapy [ 190 ].…”
Section: Overview Of Immunotherapy For Nsclcmentioning
confidence: 99%